Transcriptome and hormone Analyses reveal that melatonin promotes adventitious rooting in shaded cucumber hypocotyls - Wang, Yuping; Zhao, Hailiang; Hu, Xiaohui; Zhang, Yi; Zhang, Zicun; Zhang, Lu; Li, Lixia; Hou, Leiping; Li, Meilan (Frontiers in Plant Science, 2022)
Melatonin, a multi-regulatory molecule, stimulates root generation and regulates many aspects of plant growth and developmental processes. To gain insight into the effects of melatonin on adventitious root (AR) formation, we use cucumber seedings subjected to one of three treatments: EW (hypocotyl exposed and irrigated with water), SW (hypocotyl shaded and irrigated with water) and SM (hypocotyl shaded and irrigated with 100 µM melatonin). Under shaded conditions, melatonin induced significant AR formation in the hypocotyl. To explore the mechanism of this melatonin-induced AR formation, we used transcriptome analysis to identify 1296 significant differentially expressed genes (DEGs). Comparing SM with SW, a total of 774 genes were upregulated and 522 genes were downregulated. The DEGs were classified among different metabolic pathways, especially those connected with the synthesis of secondary metabolites, with hormone signal transduction and with plant-pathogen interactions. Analyses indicate exogenous melatonin increased contents of endogenous auxin, jasmonic acid, salicylic acid, cytokinin and abscisic acid levels during AR formation. This study indicates melatonin promotes AR formation in cucumber seedings by regulating the expressions of genes related to hormone synthesis, signaling and cell wall formation, as well as by increasing the contents of auxin, cytokinin, jasmonic acid, salicylic acid and abscisic acid. This research elucidates the molecular mechanisms of melatonin’s role in promoting AR formation in the hypocotyl of cucumber seedings under shaded conditions.